Effect of ammonium polyphosphate and fillers on flame retardant and mechanical properties of recycled PET injection molded†. (1st December 2015) - Thumsorn, Supaphorn; Negoro, Takanori; Thodsaratpreeyakul, Wiranphat; Inoya, Hiroyuki; Okoshi, Masayuki; Hamada, Hiroyuki
Abstract : Ammonium polyphosphate (APP) and inorganic fillers were applied for improving flame retardancy and mechanical performance of recycled poly(ethylene terephthalate) (RPET). RPET was compounded with 5–10 wt% of talc and glass bead using twin screw extruder then were injection molded with 2 wt% of APP. The effects of fillers contents and APP on properties and flame retardancy of RPET composites were investigated. The incorporation of talc and glass bead as well as the adding of APP significantly improved tensile and flexural modulus of RPET composites. Scanning electron microscope micrographs indicated good distribution of talc, while glass bead was agglomerated on the RPET matrix. Flame‐retardant property of neat RPET and the RPET composites revealed V‐2 of UL‐94 flammability rating. It can be noted that the composites were less dripping because of the synergistic effect of adding talc and glass bead with APP. From thermogravimetric analysis results, larger of residual char contents and lower values of the activation energy were considered for enhancing flame retardancy in the RPET composites. Copyright © 2015 John Wiley & Sons, Ltd.